STRATEGI PEMASARAN PRODUK PESTISIDA DALAM MENINGKATKAN VOLUME PENJUALAN (STUDI KASUS DI PT. PRATAMA SUMBER MILINDO SURABAYA) - Kiswandojo, Laurensius Yus Putradewa; Parsudi, Setyo; Damaijati, Effi (Agridevina : Berkala Ilmiah Agribisnis, 2016)
This study aims to identify the characteristics of the PT. Primary Source Milindo Surabaya, Analyzing internal and external factors anything that can be strengths andweaknesses, opportunities and threats in a pesticide product marketing efforts at PT. Primary Source Milindo Surabaya, Determining the most effective marketing strategies that can be applied to the PT. Primary Source Milindo Surabaya. The analytical method used is descriptive and qualitative analysis, EFE matrix, IFE matrix, and SWOT Matrix. The results of this study indicate that alternative marketing strategies are, among others, maintain the quality of products marketed, guidance and planning for employees tobe able to perform organizational tasks effectively and efficiently, maintaining a good relationship with the seller or retailer, increased sales by market segment geographictarget market, and by distribution channels are short, provide products according to customer requirements, especially in each season, improving sales promotion throughparticipating in various kinds of exhibitions organized by the City Government of Surabaya, use the internet with always up to date information, increase sales volume, providing best services to consumers so that consumers trust and loyal to pesticide products being marketed, to extend the contract period PT. Primary Source Milindo Surabaya with the retailer.